Heat and thermodynamics : An intermediate textbook - Zemansky, Mark W.; Dittman, Richard H. (Auckland : Kosaido Printing Co, 1981)
The main reason for this distribution is the deep conviction on the part of the authors that the fundamentals foundation of the subject is thermodynamics, which is well within the abilities of undergraduate students.
Part I. Fundamental concepts -- Part II. Applications if fundamentals concepts.
Includes bibliographical references and index.
Keywords: THERMODYNAMICS